Answer:
The ordinate of B exceeds the ordinate of A by 7
Step-by-step explanation:
Let
A(x1,y1),B(x2,y2)
where
x1 is the abscissa of A
x2 is the abscissa of B
y1 is the ordinate of A
y2 is the ordinate of B
we know that
[tex]m=\frac{y2-y1}{x2-x1}[/tex]
[tex]m=2[/tex]
so
[tex]2=\frac{y2-y1}{x2-x1}[/tex] -----> equation A
[tex]x2=x1+3.5[/tex] ----> equation B
substitute equation B in equation A
[tex]2=\frac{y2-y1}{x1+3.5-x1}[/tex]
[tex]2=\frac{y2-y1}{3.5}[/tex]
[tex]7=y2-y1[/tex]
[tex]y2=y1+7[/tex]
therefore
The ordinate of B exceeds the ordinate of A by 7